2020
DOI: 10.3389/fcell.2020.00549
|View full text |Cite
|
Sign up to set email alerts
|

TRPM7/RPSA Complex Regulates Pancreatic Cancer Cell Migration

Abstract: Pancreatic ductal adenocarcinoma (PDAC) is a malignancy with a very poor prognosis due to highly metastatic profile. Cell migration is an essential step of the metastatic cascade allowing cancer cells to spread toward target tissues. Recent studies strongly suggest that bioactive elastin peptides, also named elastokines or elastin-derived peptides (EDPs), are released in the extracellular microenvironment during tumoral remodeling of the stroma. EDPs stimulate cancer cell migration by interacting with their me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 35 publications
0
25
0
Order By: Relevance
“…Proteolytic cleavage of the integrinactin binding does not reduce the cell adhesion but also promote the cell migration . In fact, the upregulation of Fam38 and TRPM7 substantially facilitates the migration and invasion of cancer cells (Lefebvre et al 2020;McHugh et al 2012). In the second mechanism, the key force generator disrupting the weak adhesion contacts is stress fibers (Yumura and Fukui 1985).…”
Section: Retraction Of Stress Fibers Near the Trailing Endmentioning
confidence: 99%
“…Proteolytic cleavage of the integrinactin binding does not reduce the cell adhesion but also promote the cell migration . In fact, the upregulation of Fam38 and TRPM7 substantially facilitates the migration and invasion of cancer cells (Lefebvre et al 2020;McHugh et al 2012). In the second mechanism, the key force generator disrupting the weak adhesion contacts is stress fibers (Yumura and Fukui 1985).…”
Section: Retraction Of Stress Fibers Near the Trailing Endmentioning
confidence: 99%
“…In vivo study showed that AG-9 peptide promotes melanoma progression even more than the well described VG-6 peptide. These results were confirmed by in vitro studies in proliferation assays, migration assays, adhesion assays, proteinase secretion studies, and pseudotube formation assays to investigate angiogenesis [18,34].…”
Section: Discussionmentioning
confidence: 54%
“…Elastin was reported to interact with invasive cancer cells through RPSA [ 33 ]. Previous experiments from our laboratory identified RPSA as AG-9 receptor on HT-1080 human fibrosarcoma cell surface [ 19 ], and on MIA PaCa-2 cell pancreatic adenocarcinoma cells [ 34 ]. We first checked for RPSA expression in CAL 27 cells, compared to MIA PaCa-2 cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, TRPM7 channels are also involved in the interaction between PDAC cells and the tumoral microenvironment because TRPM7 membrane currents and TRPM7-dependent cell migration are both stimulated following treatment with elastin-derived peptides (EDP) that are released by the degradation of the extracellular matrix. Our study suggests that TRPM7 is involved in the response to EDP through its interaction with the ribosomal protein SA (RPSA) [ 93 ].…”
Section: Regulation Of Digestive Cancer Cell Fates By Magnesium Trmentioning
confidence: 99%